Pengaruh Manajemen Sumber Daya Manusia dan Budaya Organisasi terhadap Kualitas Pelayanan Guru Bimbingan Konseling - Arie Bagus Rianto; Teddy Oswari (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine and analyze the influence of human resource management and organizational culture on the quality of guidance counseling services at public high schools in Bogor City. A quantitative approach was used in this study, with a population of 10 public high schools in Bogor City. It consists of subject teachers at public high schools in Bogor City, with 140 respondents and sampling using the Slovin formula with a standard error of 5%, resulting in a sample size of 104 respondents using proportional random sampling. Data collection was conducted using a survey method and questionnaire distribution. The analysis used multiple regression testing. The results of the study showed that there was a significant positive effect of human resource management on the quality of guidance counseling services at public high schools in Bogor City. There was a significant positive effect of organizational culture on the quality of guidance counseling services at public high schools in Bogor City. There was a significant positive effect of human resource management and organizational culture on the quality of guidance counseling services at public high schools in Bogor City.